Activated Carbon, Limestone And Alginate As A Composite Adsorbent For River Water Treatment - Bukhori, Muhammad Azzim (Universiti Sains Malaysia, 2017)
Water contamination has been a serious problem to the environment and human health. It can adversely affect the human body if contaminated water is consumed regularly. Thus, wastewater treatment has been given much attention recently by the adsorption process using the low cost adsorbents. In this study, adsorption process has been recognized as one of the process that had advantages in terms of low starting cost, ease of operation and simplified design. The application of composite adsorbent such as a combination of activated carbon, limestone, alginate as a binder and molarity of calcium chloride dehydrated was carried out to assess the suitability of composite media to be applied for wastewater treatment. Two ratios of the composite adsorbent had been prepared as the media for removing turbidity and colour in wastewater. The ratios that had been prepared were AC (3): LS (7): AG (2) and AC (5): LS (5): AG (2). After prepared the composited adsorbent, a preliminary batch studies were carry out to choose the optimum conditions for the factors of every ratio. The factors that had been tested were dosages of adsorbent, contact time, shaking speed and settling time. After obtaining the optimum condition for the factors, both ratios had been tested to choose the best ratio for the adsorbent. Results showed that the optimum conditions for the factors for the ratio 3:7:2 were 9 grams of dosages of the adsorbent, 60 minutes of the contact time, 150 rpm of the shaking speed and 60 minutes of the settling time. Meanwhile, the optimum condition for the ratio 5:5:2 were 13 grams dosages of the adsorbent, 80 minutes of the contact time, 150 rpm of the shaking speed and 60 minutes of the settling time. The results for comparing both ratios showed that the ratio 5:5:2 had the higher percentage removal of turbidity and colour than ratio 3:7:2 in terms of the selecting factors.